Laws, Statutes, Ordinances, and Constitutions 18-19 (John Holt ed., 1763) - (:unkn) unknown (My University, 1763)
Ordinances of the City of New York, § XII: For every load of gunpowder, to or from the powder-house, not exceeding four casks, two shillings and six pence. If less than four casks eighteen pence. If more than four casks three shillings.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER